WEAR SIMULATION FOR ARTIFICIAL HIP JOINT BASED ON EXPERIMENTAL MODEL - 鲍雨梅; 许景顺; 吴蕾; 高海明; 徐哲玉; 马龙 (Jixie qiangdu)
HA / Zr O2 composite coating was prepared with optimized spraying parameters. Wear rate model of the coating was built with pin-on-disc tester basing on uniform design theory and the quadratic polynomial stepwise regression analysis method. Computational wear modeling based on the finite element method and the wear rate model was developed for artificial hip joint and the effect of joint clearance was investigated. It was proved by the experimental data that the wear rate model had a good forecasting effect within a wide range. The results of the wear simulation of artificial hip joint demonstrated that with the increasing of wear cycle,the contact stress on the contact surface of the joint decreased,while the worn area increased gradually,and the wear volume increased linearly but the growth rate of wear depth changed from fast to slow. What’s more,with the increasing of joint clearance,the wear volume of the acetabular decreased,but the largest wear depth increased.